Development Of Offering Module Siapsiapnikah.com Using Extreme Programming Method And Crowdsourcing Concept - Ganang Afif Rijazim; Yuli Adam Prasetyo; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract – The number of marriage in Indonesia always rising up. Around 2.250.000 marriage was held in 2012. Preparing wedding party needs so many effort, energy, and time. To help them, most of people use wedding organizer service to prepare their wedding party. Nowadays, before deciding what wedding organizer that they will use, people usually come to wedding exhibition or come to wedding organizer office. Based on survey result on this research, most of wedding organizer does not has digital media to pro mote or market their service such as website. Besides that, most of people want to find the best service of wedding organizer by searching in the internet because internet access is very easy to get now. In this research, will be discuss about developing website application for wedding organizer and wedding organizer customer in offering system with crowdsourcing concept. With this website application, customer and wedding organizer has one place to find the best wedding organizer package and service and to promote wedding organizer product and service. This website application provide two main feature, first is find and order suitable package and the second customer can customizing and order their own package to selected wedding organizer. Keywords: Wedding organizer, Website application, offering, crowdsourcing, extreme programming.